Global trade, capital flows and deglobalization: a literature review - Francesco Montaruli (Oesterreichische Nationalbank (OeNB), 2025)
This literature review connects trade and capital flows to (de)globalization, considering the main theoretical channels and empirical references to assess the current debate. The aim is to offer an integrated reference framework to study such a multifaceted global phenomenon. First, I investigate how trade and capital flows affect global integration and growth, identifying different transmission channels describing how trade and capital flows operate at the global level. Then, I examine the interplay of these driving factors of the global economy. This review is conducted both at theoretical and empirical levels, since both dimensions are necessary to understand the interplay of the economic driving forces. A range of possible quantitative instruments for future empirical analysis is reviewed. Empirically, many different approaches can be applied according to the research objective. To measure deglobalization, a longitudinal gravitational approach can be successfully used to explain global variable dynamics. Simulations of shocks or different scenarios for different blocks of countries can also be conducted as a complementary analysis with time series techniques.
Keywords: F1; F2; F3; F4; 330; globalization; deglobalization; capital flows; trade